HIV-infected patients and treatment outcomes: an equivalence study of community-located, primary care-based HIV treatment versus hospital-based specialty care in the Bronx, New York - Chu, C (2010)
The HIV-infected population in the U.S. is expanding as patients survive longer and new infections are identified. In many areas, particularly rural/medically-underserved regions, there is a growing shortage of providers with sufficient HIV expertise. HIV services incorporated into community-based, primary care settings may therefore improve the distribution and delivery of HIV treatment. Our objective was to describe/compare patients and treatment outcomes in two settings: a community-located, primary care-based HIV program and a hospital-based specialty center. Community-based providers had on-site access to generalist HIV experts. The hospital center was staffed primarily by infectious disease physicians. This was a retrospective cohort study of 854 HIV-positive adults initiating care between 1/2005 and 12/2007 within an academic medical center network in the Bronx, NY. Treatment outcomes were virologic and immunologic response at 16–32 and 48 weeks, respectively, after combination antiretroviral therapy (cART) initiation. We found that hospital-based subjects presented with a higher prevalence of AIDS (59% vs. 46%, p < 0.01) and lower initial CD4 (385 vs. 437, p < 0.05) than community-based subjects. Among 178 community vs. 237 hospital subjects starting cART, 66% vs. 62% achieved virologic suppression ([95% CI difference −0.14–0.06]) and 49% vs. 59% achieved immunologic success, defined as a 100 cell/mm(3) increase in CD4 ([95% CI difference 0.00–0.19]). The multivariate-adjusted likelihoods of achieving viral suppression (OR = 1.24 [95% CI 0.69–2.33]) and immunologic success (OR = 0.76 [95% CI 0.47–1.21]) were not statistically significant for community vs. hospital subjects. Because this was an observational study, propensity scores were used to address potential selection bias when subjects presented to a particular setting. In conclusion, HIV-infected patients initiate care at community-based clinics earlier and with less advanced HIV disease. Treatment outcomes are comparable to those at a hospital-based specialty center, suggesting that HIV care can be delivered effectively in community settings.